Circularly Polarised Luminescence from Helically Chiral "Confused" N, N, O, C‐Boron‐Chelated Dipyrromethenes (BODIPYs). Issue 11 (16th August 2017) - Clarke, Rebecca; Ho, Kin Lok; Alsimaree, Abdulrahman Abdullah; Woodford, Owen J.; Waddell, Paul G.; Bogaerts, Jonathan; Herrebout, Wouter; Knight, Julian G.; Pal, Robert; Penfold, Thomas J.; Hall, Michael J.
Abstract: Chiral organic fluorophores have significant promise in the development of efficient emitters of circularly polarized light. Herein we describe a helically chiral boron dipyrromethene (BODIPY) with a hitherto unreported N, N, O, C ‐boron‐chelation motif, synthesised by means of a one‐pot boron metathesis, nucleophilic aromatic substitution (SN Ar), Suzuki coupling, boron chelation, cascade reaction. Resolution of the racemic BODIPY (by preparative HPLC on a chiral stationary phase) allowed examination of the chiroptical properties of the resulting enantiomers ( λ max (abs)=593 nm, λ max (em)=622 nm, ϵ =30 000 m −1  cm −1, φ F =0.49, |glum |=3.7×10 −3 (hexane)). This is the first example of circularly polarised emission from a non‐ C 2 ‐symmetric helically chiral N, N, O, C ‐BODIPY and as such provides a valuable benchmark for future developments in this compound series. Abstract : Round the twist : A helically chiral boron dipyrromethene (BODIPY) with an N, N, O, C ‐boron‐chelation motif is synthesised through a one‐pot boron metathesis, nucleophilic aromatic substitution (SN Ar), Suzuki coupling, boron chelation, cascade reaction. After chiral resolution, the non‐ C 2 ‐symmetric helically chiral BODIPY demonstrated circularly polarised emission ( λ max (em)=622 nm, quantum yield φ F =0.49, |glum |=3.7×10 −3 (hexane)).